Перспективи використання комбінованих МТА при збиранні гички коренеплодів - Очеретнюк, Д. В.; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич; Ihnatiev, Yevhen (ТДАТУ, 2019)
EN: The constructive and technology scheme of sugar beet tops harvesting using integral arable and row-crop 3 kN drawbar category wheel tractor is substantiated. When using a wheel tractor of this type a necessary condition is availability of front and rear linkage mechanisms and PTO shafts, and also adjustment of its wheels to the necessary width of row-spacings sugar beet crops. Thus technology process of sugar beet tops harvesting is carried out in two stages when the defoliating machine which is frontally installed on a tractor carries out the main continuous cut of all array of tops and loads it into transport vehicle. UK: Проведений аналіз показав, що важливі проблеми збирання гички буряків цукрових можна розв'язати розробкою та застосуванням комбінованих машинно-тракторних агрегатів, які побудовані за модульним принципом і дають істотні переваги щодо їх використання у виробничих умовах.
Keywords: трактор ХТЗ-160; збирання гички; буряк цукровий; sugar beet; harvesting; beet tops; cutting; combined unit; arable and row-crop tractor; constructive and technology scheme